Capital Flows in Asia-Pacific Controls, Bonanzas and Sudden Stops - Molnar, Margit (OECD Development Centre Working Papers, 2013)
The Asia-Pacific region has long been prone to volatile capital flows that have posed a challenge for authorities to cope with and occasionally led to payment difficulties dragging down exchange rates and spilling over to the real economy. The recent global crisis repeated past history, although most economies hard hit by the 1997-1998 Asian financial crisis have learnt a lesson and are now better prepared to face volatile capital flows. Asian and Pacific countries have strengthened capital controls over 1995-2010, in particular those targeting portfolio flows. Now more countries impose some sort of control on outflows of all types of capital than 15 years ago and controls on outflows appear more stringent than on inflows. Notwithstanding the controls, most Asia-Pacific economies experienced at least one spell of large capital flows. To effectively curb capital inflow bonanzas, the measures need to be targeted. Portfolio inflow surges can be curbed by controlling bond inflows in general and in the case of very large surges, by limiting collective investment inflows. Controls on credit inflows appear effective in reducing the probability of cross-border lending booms. Furthermore, measures targeting residents appear more effective in reducing the probability of capital inflow bonanzas. Beside control measures, other conditions also appear to have a bearing on the probability of occurrence and on the length of the capital inflow spell. Previous inflows appear to be an important determinant of future booms in all asset categories, while global risk appetite increases the probability of overall inflows and cross border credit bonanzas. Domestic growth only explains the occurrence of equity portfolio inflow booms. A more lenient stance on outflows could shorten the duration of capital inflow bonanzas and hence reduce their cumulative impact on the economy